The Convents of Palermo in the Middle of the Fifteenth Century - Sardina, Patrizia (Journal of Medieval Monastic Studies, 2015)
Abstract This article investigates the finances of eight convents of Palermo in the middle of the fifteenth century, based on archival work conducted on unpublished documents. Nicolò Tudisco, archbishop of Palermo between 1435 and 1445, took part in the Council of Basle and supported the antipope Felix V. In 1443 Pope Eugenius IV levied a tax of 20,000 florins on the Sicilian Church without exempting the convents, which prompted their procurator to appeal. By comparing the tithes of these eight convents we find out that the richest of them was Santa Caterina of the Dominican Order, whose prioress, Maria Alaymo, had been dismissed in 1440. As a consequence of the tithe imposed by Callixtus III in 1456, the economic situation of Palermo’s convents had changed, but Santa Caterina remained the most important of them.